Thermoelectrically Cooled Temperature-Gradient Apparatus for Comparative Cell and Virus Temperature Studies - Clark, H. F. (1970)
Establishment of a near-linear temperature gradient in an incubator has been accomplished by the application of heat to one terminus of a conducting body, normally a metal bar, and the removal of heat from the other terminus of the conducting body. Such incubators have been complex and unwieldy because of the need for mechanical refrigeration. We have described a simplified temperature gradient incubator which uses thermoelectric module cooling coupled with electric heating. Along the gradient, 20 stations in two parallel rows of 10, each accommodating a 30-ml plastic cell culture flask, were continually monitored by an electronic thermometer, and the temperatures were recorded. By manipulation of two simple potentiometer controls, any temperature gradient between 0 and 50 C could be obtained. Minor deviations which occurred between theoretically perfect and obtained temperature gradients were reproducible and readily measured. The gradient incubator was particularly applicable to (i) simultaneously studying a given biological activity over the entire temperature range supporting the growth of a given cell, virus, or microorganism, or (ii) precisely defining the upper or lower temperature limits of a biological system by 10-point determinations. Preliminary experiments have demonstrated the usefulness of the apparatus in characterizing the temperature limits for growth in vitro of cells of reptilian cell lines. The gradient incubator was also successfully utilized for the characterization of the effect of temperature on the efficiency of plating of amphibian viruses and possible temperature variants of those viruses.